AKT and ERK dual inhibitors: The way forward?. (10th September 2019) - Cao, Zhe; Liao, Qianjin; Su, Min; Huang, Kai; Jin, Junfei; Cao, Deliang
Abstract: Phosphatidylinositol 3-kinase (PI3K)/AKT pathway regulates cell growth, proliferation, survival, mobility and invasion. Mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) pathway is also an important mitogenic signaling pathway involved in various cellular progresses. AKT, also named protein kinase B (PKB), is a primary mediator of the PI3K signaling pathway; and ERK at the end of MAPK signaling is the unique substrate and downstream effector of mitogen-activated protein/extracellular signal-regulated kinase (MEK). The AKT and ERK signaling are both aberrantly activated in a wide range of human cancers and have long been targeted for cancer therapy, but the clinical benefits of these targeted therapies have been limited due to complex cross-talk. Novel strategies, such as AKT/ERK dual inhibitors, may be needed. Highlights: Aberrant activation and oncogenesis of PI3K/AKT and MAPK/ERK pathways in cancer. Cross-talk between the PI3K/AKT and MAPK/ERK pathways drives drug resistance. Dual inhibitors of AKT and ERK yield clinical benefits in targeted cancer therapy.